Thermo-physical and mechanical properties of five wood species grown in Abeokuta, Ogun State, Nigeria (2011)
"Thermal conductivity, toughness, cleavability tensile and bending strengths of Khaya senegalensis (Oganwo), Nauclea diderrichii (Opepe), Triplochiton scleroxylon (Arere), Pycnanathus angolensis (Akomu), Albizia zygia (Ayunre) grown in Ogun State, Nigeria were investigated to obtain preliminary data on these properties to guide utilization. The thermal conductivity was measured using fully automated unitherm 6000 Guarded Hot Plate (-170 to 550°) while the tensile and bending strengths of the woods were evaluated using INSTRON 5500 series Electromechanical Testing Machine configured with the 2820 series base beam and three-point anvil settings based on ASTM 52188 and ASTM 52186 recommendation respectively. The toughness analysis was carried out in accordance to ASTM D6110-97 using Charpy Notched method while the cleavability of the wood was determined using a static testing arrangement. Results indicated that the thermal conductivity of these five wood species ranged from 0.20-0.26 W/m.k. with Opepe and Arere having the lowest thermal conductivity of 0.21W/m.k. The toughness of Oganwo (73.16 J/cm) and Opepe (67.27 J/cm) was the highest and lowest respectively thereby making Opepe the most amenable to splitting and use for firewood. The values obtained for tensile and bending strengths are in increasing order from Opepe, Akomu, Arere, Ayunre to Oganwo. Oganwo has the maximum values for all the properties investigated. This study was able to generate data on specified properties for Opepe, Akomu, Arere, Ayunre and Oganwo grown in Abeokuta, Ogun State while also establishing the need to be conservative in the use of these five wood species. "